Students' Learning Experiences With LMS Tes Teach In Flipped-Class Instruction - Zainuddin, Zamzami; Hermawan, Hardika Dwi; Nuraini, Febritesna; Prayitno, Santo Mugi (Elinvo (Electronics, Informatics, and Vocational Education), 2019)
The purpose of this study was to identify the impact of implementing a Learning Management System (LMS) "˜TES Teach' on students' learning experiences in a computer-assisted language learning (CALL) course with flipped-class instruction. For the data collection procedure, an individual interview with ten undergraduate students from an Indonesian college was conducted to demonstrate the potential impacts of the LMS in students' meaningful learning activities. The observation of students' learning activities on the LMS was also recorded to support the interview data. The LMS was adopted to distribute and receive information, thus, the students were able to monitor learning activities, learn the contents before coming to class, evaluate learning process, and interact with others outside of class hours. The finding of this study suggests that the LMS TES Teach is recommended to be performed in teaching CALL for higher education in Indonesia. It offers students' occasion to practice and enhances their listening, writing, reading and vocabulary skills in and out-of-class times. It also prepares students to get ready for classroom activities in term of conversations and speaking skills. The further use of the LMSs should become often-visited sites by students for learning activities and replaced other non-educational favorite websites. Finally, this study recommends that the Ministry of Research, Technology and Higher education or policymakers in Indonesia, including instructors, students, and community members, must be actively involved in developing, supporting, and maintaining a transformed learning culture, from being traditional to a technology-based learning environment.